Eye movements, attention, and expert knowledge in the observation of Bharatanatyam dance - Raganya Ponmanadiyil; Matthew Harold Woolhouse (Bern Open Publishing, 2018)
Previous research indicates that dance expertise affects eye-movement behaviour-dance experts tend to have faster saccades and more tightly clustered fixations than novices when observing dance, suggesting that experts are able to predict movements and process choreographic information more quickly. Relating to this, the present study aimed to explore (1) the effects of expertise on eye movements (as a proxy for attentional focus and the existence of movement-dance schemas) in Indian Bharatanatyam dance, and (2) narrative dance, which is an important component of Bharatanatyam. Fixation durations, dwell times, and fixation-position dispersions were recorded for novices and experts in Bharatanatyam (N = 22) while they observed videos of narrative and non-narrative Bharatanatyam dance. Consistent with previous research, experts had shorter fixation durations and more tightly clustered fixations than novices. Tighter clustering of fixations was also found for narrative dance versus non-narrative. Our results are discussed in relation to previous dance and eye-tracking research.